Stress-Softening and Interaction in Polydimethylsiloxane/Nano-Calcium Carbonate Networks - Peng, Ya; Lu, Shoutao; He, Yi; Zhao, Guangbin; Zhang, Ying; Ge, Cui (Asian Journal of Chemistry, 2012)
In this study, stress-softening and interaction in polydimethylsiloxane and nano-calcium carbonate was invested to understand the mechanism of reinforcement. The stress-softening found in both unfilled and filled polydimethylsiloxane was more prominent in filled polydimethylsiloxane, particularly for samples with high filler content. The interaction between polydimethylsiloxane and nano-calcium carbonate was verified by swelling experiment, cross-linking density measurement, dynamic laser light scattering and IR experiment. The results demonstrate that the interaction can be attributed to the branched chain structure of nano-CaCO3 and active groups on the surface of nano-CaCO3.